Vegetable Pesticides and Planting Spattern Againt Grayak Caterpillar (Spodoptera exigua) Attacks on long Beans (Vigna Sinensis L.) - Pratama, Yuda Rizky; Idris, M.; Idami, Zahratul (Jurnal Biologi Tropis, 2025)
: The armyworm (Spodoptera exigua) is one of the most common plant pests that lower plant yields.  The purpose of this study is to ascertain how armyworm (Spodoptera exigua) attacks on long bean plants are impacted by botanical pesticides and planting distance.  This study employs experiments and is quantitative in nature.  In this investigation, papaya leaf trials and garlic peels were used as plant insecticides in covert studies.  The one-way ANOVA test was the statistical method employed in this investigation. The findings demonstrated that while the botanical concentration had no effect on plant height or attack severity, it significantly affected the percentage of attacks and the leaf area index.  Plant height, attack intensity, attack %, and leaf area index were not significantly affected by planting distance in long bean plants.  The study's conclusions include the need for more research on plant insecticides that use plant leaves to fend against attacks, particularly in lowering the incidence of armyworm attacks.